REKONSTRUKSI MODEL STUDI KELAYAKAN BISNIS SYARIAH BERBASIS MAQ??ID AL-SYAR?‘AH ANALISIS NORMATIF TERHADAP UMKM DAN STARTUP SYARIAH - Syai'in; Sulung Rahmawan Wira Ghani (Smart Education, 2026)
The development of Sharia-based micro, small, and medium enterprises (MSMEs) and startups in Indonesia has grown significantly alongside the strengthening of the national halal ecosystem and supportive government regulations. However, business feasibility studies applied in practice are still largely dominated by conventional approaches that emphasize profitability and financial sustainability. Meanwhile, Sharia business feasibility analysis generally remains limited to compliance with the prohibition of riba, gharar, and maysir. This situation indicates a conceptual gap in integrating maq??id al-shar?‘ah as an evaluative framework in business feasibility analysis. This study aims to reconstruct a maq??id-based Sharia business feasibility model that can serve as an evaluative instrument for Sharia MSMEs and startups. The research employs a normative legal research method using conceptual and analytical approaches to the theory of maq??id al-shar?‘ah in Islamic economic law. The findings reveal that Sharia business feasibility studies can be reconstructed through a three-layer model consisting of sharia screening, business feasibility analysis, and maq??id impact assessment. The integration of the five essential objectives of maq??id—?if? al-d?n, ?if? al-nafs, ?if? al-‘aql, ?if? al-nasl, and ?if? al-m?l—demonstrates that business feasibility should not only be measured by Sharia compliance and profitability but also by its contribution to social welfare and sustainable economic development.